Coaching Effectiveness Framework - Joanna Jarosz; Rick Cartor (International Journal of Evidence Based Coaching and Mentoring)
Despite increased empirical research, coaching effectiveness in organizations has not been fully established. Leveraging the ‘Cube of Coaching Effectiveness’, this study reviews scientific literature and further integrates findings from qualitative and quantitative research, coaching effectiveness questionnaire validation, insights from global data on coaching outcomes and from the interviews with coaches. The paper introduces the ‘Coaching Effectiveness Framework’ to define and measure coaching effectiveness, focusing on competencies, behaviors, and outcomes for organizational application, including enhancement of employee development. Highlighting key skills and behaviors for effective coaching, the framework offers practical insights for coaching training and warrants further empirical validation in organizational contexts.